Fast food outlets: an empirical analysis on customer expectations and perceptions - Naila Aaijaz; Mohamed Dahlan Ibrahim (2011)
Using the data from a consumer survey, this study aims to investigate the relationship between consumers’ fast food outlet loyalty (in years) and the attitude of young consumers living in Kota Bharu city. The study also investigates the importance of quality of the product that are offered to the customer. It also studies the importance of facility location and layout which bring convenience to the customer and increase efficiency at the outlets. One step further we also walkthrough the service delivery process and service package offered when dealing with customers by fast food outlets. This study was conducted via undergraduate business course students of University Malaysia Kelantan (UMK) who as young customers filled a self-administered brief questionnaire on their visits to various fast food outlets in Kota Bharu, Kelantan State Malaysia. The results indicate that food quality, overall cleanliness of the outlet, service efficiency and facility layout provided by the outlet influences the fast food brand loyalty of young customers. Purchases were mainly due to the four factors-perception of customers on food quality, cleanliness, facility layout, efficiency in service delivery. The research was conducted with students, and while these represent a key target market, any further research should target a more diverse public base. Despite research suggesting a general lack of food quality technical knowledge, results from this 168 person sample indicated familiarity with general likeable quality in food served at fast food outlets by young consumers, general clean conditions maintained in the outlets and facilities provided to attract more customers. There are important implications for global fast-food companies in terms of protecting and developing their brand value; they need to respond to the wider food-related debates in society, in particular those concerning food quality, cleanliness and fast food service package offerings. This will ensure their consistency with brand loyalty and customer retention initiatives. The value of this paper lies in its consumer value in the Malaysian fast food industry as it explores the same through the perceptions and expectations of young consumers of fast food.